Singular Curves on K3 Surfaces - Ballico, E.; Fontanari, C.; Tasin, L. (Sarajevo Journal of Mathematics, 2024)
We investigate the Clifford index of singular curves on K3 surfaces by following the lines of [10]. As a consequence, we are able to deduce from [3] that Green's conjecture holds for all integral curves on K3 surfaces. 2000 Mathematics Subject Classification. 14H51